Colder environments did not select for a faster metabolism during experimental evolution of Drosophila melanogaster - Alton, Lesley A.; Condon, Catriona; White, Craig R.; Angilletta, Michael J. (Evolution, 2017)
The effect of temperature on the evolution of metabolism has been the subject of debate for a century; however, no consistent patterns have emerged from comparisons of metabolic rate within and among species living at different temperatures. We used experimental evolution to determine how metabolism evolves in populations of Drosophila melanogaster exposed to one of three selective treatments: a constant 16°C, a constant 25°C, or temporal fluctuations between 16 and 25°C. We tested August Krogh’s controversial hypothesis that colder environments select for a faster metabolism. Given that colder environments also experience greater seasonality, we also tested the hypothesis that temporal variation in temperature may be the factor that selects for a faster metabolism. We measured the metabolic rate of flies from each selective treatment at 16, 20.5, and 25°C. Although metabolism was faster at higher temperatures, flies from the selective treatments had similar metabolic rates at each measurement temperature. Based on variation among genotypes within populations, heritable variation in metabolism was likely sufficient for adaptation to occur. We conclude that colder or seasonal environments do not necessarily select for a faster metabolism. Rather, other factors besides temperature likely contribute to patterns of metabolic rate over thermal clines in nature.